Involvement of spinal α₂-adrenoceptors in prolonged modulation of hind limb withdrawal reflexes following acute noxious stimulation in the anaesthetized rabbit - Harris, John (Wiley, 2016)
The role of spinal α₂-adrenoceptors in mediating long-lasting modulation of hind limb withdrawal reflexes following acute noxious chemical stimulation of distant heterotopic and local homotopic locations has been investigated in pentobarbitone-anaesthetized rabbits. Reflexes evoked in the ankle extensor muscle medial gastrocnemius (MG) by electrical stimulation of the ipsilateral heel, and reflexes elicited in the ankle flexor tibialis anterior and the knee flexor semitendinosus by stimulation at the base of the ipsilateral toes, could be inhibited for over 1 h after mustard oil (20%) was applied to either the snout or into the contralateral MG. The heel–MG response was also inhibited after applying mustard oil across the plantar metatarsophalangeal joints of the ipsilateral foot, whereas this homotopic stimulus facilitated both flexor responses. Mustard oil also caused a significant pressor effect when applied to any of the three test sites. The selective α₂-adrenoceptor antagonist, RX 821002 (100–300 μg, intrathecally), had no effect on reflexes per se, but did cause a decrease in mean arterial blood pressure. In the presence of the α₂-blocker, inhibitory and facilitatory effects of mustard oil on reflexes were completely abolished. These data imply that long-lasting inhibition of spinal reflexes following acute noxious stimulation of distant locations involves activation of supraspinal noradrenergic pathways, the effects of which are dependent on an intact α₂-adrenoceptor system at the spinal level. These pathways and receptors also appear to be involved in facilitation (sensitization) as well as inhibition of reflexes following a noxious stimulus applied to the same limb.